Penerapan Iptek melalui kukerta terintegrasi pengembangan mata pencaharian alternatif dengan teknologi “bule empal” bersama kelompok usaha mandiri Kota Pekanbaru - Muhammad Fauzi; Eko Prianto; Bintal Amin; Andri Hendrizal; Iskandar Putra; Muhammad Bintang Anto Mycawa; Nona Mutiara Sari (Unri Conference Series: Community Engagement, 2021)
The economic level of the city of Pekanbaru experienced a significant increase in 2019 which was 6.01% from previous years, but since the Covid-19 pandemic outbreak in 2020, the economic condition of the city of Pekanbaru has decreased by around 2.3%. This figure is considered quite worrying for the economic condition of the people of Pekanbaru City if there are no efficient steps to overcome it.Currently the people of Pekanbaru City are required to be more innovative in utilizing existing resources by considering the narrow and limited urban conditions. Cultivation of catfish (Clarias gariepinus) by utilizing tarpaulin buckets "Bule Empal - Catfish Cultivation Bucket Tarpaulin" is one of the innovations in developing alternative livelihoods for people in urban areas who have narrow land with a relatively short maintenance time of about 3 months. In order to implement the Tri Dharma of Higher Education, namely Education, Research, and Service. Academics can provide guidance through knowledge transfer activities, applications and assistance to community business groups to apply Bule Empal "Catfish Aquaculture with Tarpaulin Buckets" in the context of developing alternative livelihoods for the community in the midst of economic problems due to the COVID-19 pandemic. With this integrated Kukerta, the potential for neglected yards can be raised for cultivation. This shows that the touch of science and technology through integrated Kukerta is able to accelerate the development of catfish farming in the Binawidya Village of Kota Pekanbaru.